Managing schema evolution in a federated spatial database system - Wu, Xiaoying; Xia, Jianhong (Cecilia); West, Geoffrey; Arnold, L.; Veenendaal, Bert (IGI Global, 2012)
A Federal Spatial Database System (FSDBS) is the integration of multiple spatial data sources and the realisation of effective spatial data sharing. These are becoming increasingly popular as more and more spatial and non-spatial datasets are integrated, especially those across a number of independent organisations. However, in a FSDBS environment, database schemas are subject to change and the management of these changes is complex and inefficient. This is because schema changes in one local database will invalidate applications built against this local schema, but also applications built against the global schema. The research is motivated by developments in the Shared Land Information Platform, built by Landgate in Western Australia as a Spatial Data Infrastructure enabler that has been running since 2007. The more than 350 datasets in SLIP are from and controlled by 20 organisations with queries built over the different datasets. Changes in the various databases require schema updating to be streamlined. In this chapter, an Automatic Schema Evolution Framework is explored and developed to more effectively manage schema evolution in a FSDBS. This framework provides a Schema Element Dependency Meta-Model, a set of Schema Change Templates, and incorporates view generation, view rewriting, and query rewriting as solutions. These developed methods ensure applications can accommodate schema changes and hence remain valid.